O jogo na comunidade de Caravelas-BA : variação da fricativa coronal pós-vocálica - Lima, Jares Gomes (2017)
This study is a sociolinguistic analysis on the variation of the post-vocalic fricative in light of the Theory of Variation and Linguistic Change (LABOV, 2008 [1972]; WEINREICH, LABOV & HERZOG, 2006 [1968]). We studied the speech community of Caravelas, located in the extreme south of Bahia state. Because there is no speech databases of this area, it was necessary to build our own corpus. The sample is stratified by sex/gender (male/female), schooling (1-8 years; 9-11 years; more than 11 years) and by age group (15-25 years; 26-49 years and more than 49 years). We intend to record 36 speakers in the end; 25 were used here. In Caravelas, the analyzed variation happens in a very specific environment, before [t] and/or the affricate [?], by means of two voiceless fricatives: [s] and [?]. For the statistical analysis, we used the program GoldVarb X (SANKOFF, TAGLIAMONTE & SMITH, 2005), in order to verify the productions of the palatalized variant [?] in contrast to the alveolar production [s]. A pilot analysis was also performed with statistical tests using the platform R (R CORE TEAM, 2013), in order to know the characteristics of the data considered as ambiguous between alveopalatal and alveolar. We observes in Praat (BOERSMA & WEENINK, 2013) the frequencies of the spectral peaks, obtained from the repetitions of 11 words, totaling 312 repetitions, through the reading of a text written by 04 informants. For this, we used the Speech Production Theories, specifically the theory of perturbation (KENT & READ, 2015). In the general analysis of the data in GoldVarb X, the variables schooling and sex/gender were considered statistically significant. In a cross-sectional analysis of schooling and sex/gender, the variable age group also presented statistical significance. The results show that individuals over 49 years of age, as well as women, are the ones that present the highest statistical significance for palatalized production. However, with more than 11 years of schooling, women and men present different effects, since, in the case of men, they disfavor the alveopalatal variant, while women tend to favor it. There is a tendency for the palatalized variant in speakers from 9 to 11 years of schooling for both the female and the male groups. The statistically significant structural variables were (1) coda position, (2) quality of the preceding vowel, (3) quality of the next consonant segment and (4) syllable stress. The alveopalatal variant is favored by the medial coda, by the following affricated consonant, and by the [+ posterior] trace of the preceding vowels, being [u] and [?], followed by the [+ high] trait, with [i]. The post-tonic position disfavor the palatalized variant. In this way, social and structural factors are important for the understanding of the variation analyzed, which does not present itself as a phenomenon of linguistic change. The pilot acoustic analysis, in turn, allowed us to progress in the understanding of auditory doubts, since it revealed more previous constrictions, causing higher frequency means of the spectral peaks of the cases considered doubtful in the repetitions.